Evaluating Nicotinamide Adenine Dinucleotide for Its Effects on Halo Blight of Snap Bean - Huang, Yi (Plant disease, 2023)
Halo blight, caused by Pseudomonas syringae pv. phaseolicola, is one of the major bacterial diseases on snap bean in Florida, and the outbreaks of this disease have occurred more often in recent years. Current management of this disease primarily depends on application of fixed copper-based bactericides but climate change and resistance development in the pathogen populations still cause hardship for management of this disease, especially in south Florida. In this study, nicotinamide adenine dinucleotide (NAD+) was evaluated in the greenhouse for its potential to reduce halo blight on snap bean. When NAD+ at 5 mM was applied by soil drench, foliar spray, or leaf infiltration, NAD+ significantly (P < 0.05) reduced disease severity of halo blight on snap bean compared with the untreated control. When NAD+ was applied by leaf infiltration, among the tested concentrations, NAD+ at 0.5 to 1.0 mM was most effective in decreasing halo blight disease. NAD+ at 2.5 mM applied as a foliar spray in rotation with Kocide 3000 (copper hydroxide) at 0.5 mg/ml further reduced disease severity compared with Kocide 3000 alone. In the in vitro study, no inhibitory effects of NAD+ were detected on the bacterial pathogen P. syringae pv. phaseolicola. Results of real-time PCR showed that the defense-related genes PR1, AZI1, EDS1, SARD1, PDF1.2, and PAL1 were upregulated in the NAD+ treatment. Taken together, these data indicated that NAD+ significantly suppressed halo blight on snap bean, and application of NAD+ has the potential in management of this important disease